2005
DOI: 10.1016/j.cellbi.2004.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Human neuroblastoma GOTO cells express CD44 and localize it into lipid rafts upon differentiation into Schwannian cells

Abstract: Neuroblastoma, which is a malignant tumor consisting of dedifferentiated neuroectodermal cells, is known to show spontaneous maturation or regression in its growth. Cultured human neuroblastoma GOTO cells could be induced to differentiate into Schwannian cells and neuronal cells by incubation in the presence of 5-bromo-2'-deoxyuridine (BrdU) and by serum depletion, respectively. Here we report that in association with these differentiations, cells differentiated into Schwannian cells specifically expressed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The GOTO-derived cell line also expressed myelin-specific proteins to a limited extent [48]. Recently, it has been reported that when GOTO cells differentiate into Schwann-like cells, they express CD44 and localize this molecule to lipid rafts which is characteristic of Schwann cells in culture [65].…”
Section: Goto Human Schwann Cell Line: Origin and Characteristicsmentioning
confidence: 99%
“…The GOTO-derived cell line also expressed myelin-specific proteins to a limited extent [48]. Recently, it has been reported that when GOTO cells differentiate into Schwann-like cells, they express CD44 and localize this molecule to lipid rafts which is characteristic of Schwann cells in culture [65].…”
Section: Goto Human Schwann Cell Line: Origin and Characteristicsmentioning
confidence: 99%
“…In order to evaluate the capacity of each of the cell lines to differentiate towards glial lineage, BrdU was used as previously described [ 11 , 26 ].…”
Section: Differentiation Studiesmentioning
confidence: 99%
“…Bromodeoxyuridine is a thymidine analog which incorporates into the newly synthesized DNA during the S phase of cell cycle. It has been used as a glial differentiation factor in vitro for NB, inducing cell flattening and increased substrate adhesiveness [ 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were supported by a study which reported that cultured human neuroblastoma GOTO cells, of which a cell adhesion molecule CD44 expression is usually suppressed, could be induced to differentiate into Schwannian cells and neuronal cells in the presence of 5-bromo-2’-deoxyuridine (BrdU) and by serum depletion respectively. These GOTO cells differentiated into Schwannian cells, specifically expressed CD44 glycoprotein, while this molecule remained suppressed in cells differentiated into neuronal cells which suggests that CD44 might play an important role in GOTO cells differentiation into Schwannian cells [36] and thus in tumor evolution into maturing subtypes.…”
Section: Discussionmentioning
confidence: 99%